Structure and Composition of the 200 K‐Superconducting Phase of H2S at Ultrahigh Pressure: The Perovskite (SH−)(H3S+). Issue 11 (8th February 2016) - Gordon, Elijah E.; Xu, Ke; Xiang, Hongjun; Bussmann‐Holder, Annette; Kremer, Reinhard K.; Simon, Arndt; Köhler, Jürgen; Whangbo, Myung‐Hwan
Abstract: At ultrahigh pressure (>110 GPa), H2 S is converted into a metallic phase that becomes superconducting with a record Tc of approximately 200 K. It has been proposed that the superconducting phase is body‐centered cubic H3 S (Im 3 ‾ m, a=3.089 Å) resulting from the decomposition reaction 3 H2 S→2 H3 S+S. The analogy between H2 S and H2 O led us to a very different conclusion. The well‐known dissociation of water into H3 O + and OH − increases by orders of magnitude under pressure. H2 S is anticipated to behave similarly under pressure, with the dissociation process 2 H2 S→H3 S + +SH − leading to the perovskite structure (SH − )(H3 S + ). This phase consists of corner‐sharing SH6 octahedra with SH − ions at each A site (the centers of the S8 cubes). DFT calculations show that the perovskite (SH − )(H3 S + ) is thermodynamically more stable than the Im 3 ‾ m structure of H3 S, and suggest that the A site hydrogen atoms are most likely fluxional even at Tc  . Abstract : Under ultrahigh pressure (>110 GPa), H2 S is converted into a metallic phase that becomes superconducting with a record T c of approximately 200 K. It is proposed that in this phase a dissociation of 2 H2 S into H3 S + and SH − is present, leading to the perovskite structure (SH − )(H3 S + ). This phase consists of corner‐sharing SH6 octahedra with SH − ions at the center of each S8 cube.